Half-cell edge passivation method
The cutting surface of the half-cell is passivated and repaired by Ga2O3/Al2O3 double-layer composite coating, which solves the problem of difficulty in obtaining high-quality Al2O3 films in the prior art, and achieves a more efficient passivation effect and lower energy loss.
Patent Information
- Application Number
- CN202411813113.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-18
AI Technical Summary
It is difficult to obtain high-quality Al2O3 films in the prior art, resulting in poor passivation effect of the edge of the half-piece battery, increasing energy loss and affecting production capacity.
The cutting surface of the half-cell was passivated and repaired by using Ga2O3/Al2O3 double-layer composite coating. The thickness of the Ga2O3 film layer was 3-5nm and the thickness of the Al2O3 film layer was 15-30nm. It was subjected to ALD deposition and annealing.
The passivation performance of the edge of the half-cell battery is improved, pFF loss is reduced, the power of the component is increased, and energy loss is reduced.
Smart Images

Figure CN119653907A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of half-cell battery edge passivation, and in particular to a method for half-cell battery edge passivation. Background Art
[0002] With the popularization of cell slicing, shingling, and assembling technologies, the use of lasers to cut whole cells has gradually become the mainstream trend in the industry. However, it has been found in practice that after cutting the cell with lasers, the specific surface area of the cell edge increases, resulting in edge recombination losses, causing a decrease in open circuit voltage, and then leading to a loss of efficiency of crystalline silicon solar cells of more than 0.2%. Studies have found that the main reasons are mainly due to the following points: 1. New edges will be generated after cutting half or multiple cells, and cutting will destroy the interface characteristics of the cell edge surface; 2. The lattice structure is interrupted on the surface, and a large number of dangling bonds are generated on the new edge surface and surface recombination centers (edge recombination) are formed; 3. Cutting damage will cause many defects and lattice distortions, forming more recombination centers and reducing the minority carrier lifetime; 4. If the exposed new edge is not passivated, it will cause efficiency loss and reliability decline, resulting in reduced battery electrical performance.
[0003] The existing technology usually uses Al2O3 film to passivate and repair the cut surface of the half-cell battery to reduce edge carrier recombination and improve the passivation performance of the cut cell edge. However, it is difficult to obtain a high-quality Al2O3 film due to the flatness of the cut surface. In order to obtain a high-quality passivation effect, the thickness of the Al2O3 film usually needs to be set between 50-100nm or even thicker, which will increase the process time, increase energy loss and affect production capacity. Summary of the invention
[0004] In order to overcome the problems in the prior art that it is difficult to obtain a high-quality Al2O3 film and that an excessively thick Al2O3 film leads to increased energy loss, the present invention provides a method for edge passivation of a half-cell battery, comprising the following steps:
[0005] Step 1: Cut the battery cell into half cells;
[0006] Step 2: Clean the cut surface of the half-cell battery;
[0007] Step 3: After cleaning, deposit Ga2O3 film layer and Al2O3 film layer on the cut surface of the half-cell in sequence;
[0008] Step 4: Annealing the Ga2O3 film layer and the Al2O3 film layer;
[0009] Step 5: Inspect, sort and package the half-cell after annealing.
[0010] Preferably, an ALD deposition method is adopted, and a Ga2O3 film layer is deposited on the cut surface of the half-cell using a gallium source precursor and an oxygen source, and the thickness of the Ga2O3 film layer is 3-5 nm.
[0011] Preferably, the gallium source precursor is one or more of trimethylgallium, triethylgallium and gallium trichloride.
[0012] Preferably, an ALD deposition method is adopted, and an aluminum source precursor and an oxygen source are used to deposit an Al2O3 film layer on the surface of the Ga2O3 film layer, and the thickness of the Al2O3 film layer is 15-30 nm.
[0013] Preferably, the aluminum source precursor is one or more of aluminum trichloride, trimethylaluminum and triethylaluminum.
[0014] Preferably, it is characterized in that the oxygen source is one or more of H2O, O2, and O3.
[0015] Preferably, the deposition temperature is 200-230° C., and the isolation gas used is one or more of helium, argon and nitrogen.
[0016] Preferably, the cutting of the battery cell includes: using a pulsed laser to make grooves at both ends of the cutting line of the battery cell, and then using a continuous laser to heat the battery cell and atomize and cool the battery cell to obtain a half-cell.
[0017] Preferably, plasma treatment is used to clean the cut surface of the half-cell.
[0018] Preferably, the annealing temperature is 250-300°C.
[0019] Beneficial effects:
[0020] The beneficial effects produced by the technical solution of the present invention are as follows:
[0021] The present invention adopts Ga2O3 / Al2O3 double-layer structure composite coating to passivate and repair the cut surface of the half-cell battery. Ga2O3 is a transparent conductive oxide material with excellent performance, large bandgap width, high breakdown field strength, and small on-resistance. Moreover, as an insulating material, Ga2O3 has high-k characteristics and can be used as a passivation film to eliminate or reduce interface states. In addition, the strong passivation of Ga2O3 can reduce the interface state of the cut surface of the half-cell battery while providing a smooth plane for the subsequent deposition of the Al2O3 film, thereby greatly enhancing the passivation effect of the Al2O3 film, improving the passivation performance, reducing the pFF loss of the half-cell battery, and improving the power of the component. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 It is the AFM test result diagram of Example 1, Comparative Example 1 and Comparative Example 2 in the present invention. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the present invention will be clearly and completely described in conjunction with the embodiments below. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Therefore, the following detailed description of the embodiments of the present invention provided is not intended to limit the scope of the claimed invention, but merely represents the selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0025] This embodiment adopts Ga2O3 / Al2O3 double-layer structure to passivate and repair the cut surface of half-cell to solve the problems of difficulty in obtaining high-quality Al2O3 film and increased energy loss caused by excessive thickness of Al2O3 film. The specific implementation is as follows:
[0026] A method for edge passivation of a half-cell battery comprises the following steps:
[0027] Step 1: Cut the battery cell into half cells;
[0028] Step 2: Clean the cut surface of the half-cell battery;
[0029] Step 3: After cleaning, deposit Ga2O3 film layer and Al2O3 film layer on the cut surface of the half-cell in sequence;
[0030] Step 4: Annealing the Ga2O3 film layer and the Al2O3 film layer;
[0031] Step 5: Inspect, sort and package the half-cell after annealing.
[0032] Specifically, an ALD deposition method is adopted, and a Ga2O3 film layer is deposited on the cut surface of the half-cell using a gallium source precursor and an oxygen source, and the thickness of the Ga2O3 film layer is 3-5 nm.
[0033] Specifically, the gallium source precursor is one or more of trimethylgallium, triethylgallium and gallium trichloride.
[0034] Specifically, an ALD deposition method is adopted, and an aluminum source precursor and an oxygen source are used to deposit an Al2O3 film layer on the surface of the Ga2O3 film layer, and the thickness of the Al2O3 film layer is 15-30 nm.
[0035] Specifically, the aluminum source precursor is one or more of aluminum trichloride, trimethylaluminum and triethylaluminum.
[0036] Specifically, it is characterized in that the oxygen source is one or more of H2O, O2, and O3.
[0037] Specifically, the deposition temperature is 200-230° C., and the isolation gas used is one or more of helium, argon and nitrogen.
[0038] Specifically, the cutting of the battery cell includes: using a pulsed laser to make grooves at both ends of the cutting line of the battery cell, and then using a continuous laser to heat the battery cell and atomize and cool the battery cell to obtain a half-cell cell.
[0039] Specifically, plasma treatment is used to clean the cut surface of the half-cell.
[0040] Specifically, the annealing temperature is 250-300°C.
[0041] The present invention will be further described below through specific examples and comparative examples:
[0042] Example 1
[0043] In this embodiment, the steps of edge passivation of a half-cell battery include:
[0044] Step 1: Use a pulsed laser to make grooves at both ends of the cell's dividing line, then use a continuous laser to heat the cell and atomize and cool the cell, forming a temperature gradient to cause the cell to split along the dividing line under thermal stress to obtain a half cell;
[0045] Step 2: Place the obtained half-cell batteries in groups of 1,200 horizontally in a cell box, and make the cut surfaces of all the half-cell batteries be on the same horizontal plane, and then perform plasma treatment on the cut surfaces of the half-cell batteries;
[0046] Step 3, placing the half-cell obtained in step 2 into an oxidation deposition device, and using an ALD deposition method, N2 as an isolation gas, trimethylgallium as a gallium source precursor, and O3 as an oxygen source to coat a layer of Ga2O3 film on the cut surface of the half-cell at 220°C. The thickness of the Ga2O3 film is 5nm;
[0047] Step 4: A layer of Al2O3 film is deposited on the surface of the Ga2O3 film by using ALD deposition method at 220° C., using N2 as isolation gas, trimethylaluminum as aluminum source precursor, and H2O as oxygen source. The thickness of the Al2O3 film is 30 nm.
[0048] Step 4: After the coating is completed, the Ga2O3 / Al2O3 composite film is annealed at 260°C;
[0049] Step five: inspect, sort and package the half-cell batteries after annealing.
[0050] Example 2
[0051] In this embodiment, the steps of edge passivation of a half-cell battery include:
[0052] Step 1: Use a pulsed laser to make grooves at both ends of the cell's dividing line, then use a continuous laser to heat the cell and atomize and cool the cell, forming a temperature gradient to cause the cell to split along the dividing line under thermal stress to obtain a half cell;
[0053] Step 2: Place the obtained half-cell batteries in groups of 1,200 horizontally in a cell box, and make the cut surfaces of all the half-cell batteries be on the same horizontal plane, and then perform plasma treatment on the cut surfaces of the half-cell batteries;
[0054] Step 3, placing the half-cell obtained in step 2 into an oxidation deposition device, and using an ALD deposition method, He as an isolation gas, triethylgallium as a gallium source precursor, and O2 as an oxygen source to coat a layer of Ga2O3 film on the cut surface of the half-cell at 200°C, wherein the thickness of the Ga2O3 film is 3nm;
[0055] Step 4: A layer of Al2O3 film is deposited on the surface of the Ga2O3 film by using ALD deposition method at 200° C., using He as the isolation gas, triethylaluminum as the aluminum source precursor, and H2O as the oxygen source. The thickness of the Al2O3 film is 15 nm.
[0056] Step 4: After the coating is completed, the Ga2O3 / Al2O3 composite film is annealed at 250°C;
[0057] Step five: inspect, sort and package the half-cell batteries after annealing.
[0058] Example 3
[0059] In this embodiment, the steps of edge passivation of a half-cell battery include:
[0060] Step 1: Use a pulsed laser to make grooves at both ends of the cell's dividing line, then use a continuous laser to heat the cell and atomize and cool the cell, forming a temperature gradient to cause the cell to split along the dividing line under thermal stress to obtain a half cell;
[0061] Step 2: Place the obtained half-cell batteries in groups of 1,200 horizontally in a cell box, and make the cut surfaces of all the half-cell batteries be on the same horizontal plane, and then perform plasma treatment on the cut surfaces of the half-cell batteries;
[0062] Step 3, placing the half-cell obtained in step 2 into an oxidation deposition device, and using an ALD deposition method, Ar as an isolation gas, gallium trichloride as a gallium source precursor, and O3 as an oxygen source to coat a layer of Ga2O3 film on the cut surface of the half-cell at 230°C, wherein the thickness of the Ga2O3 film is 4nm;
[0063] Step 4: A layer of Al2O3 film is deposited on the surface of the Ga2O3 film by using ALD deposition method at 230° C., using Ar as the isolation gas, aluminum chloride as the aluminum source precursor, and H2O as the oxygen source. The thickness of the Al2O3 film is 23 nm.
[0064] Step 4: After the coating is completed, the Ga2O3 / Al2O3 composite film is annealed at 300°C;
[0065] Step five: inspect, sort and package the half-cell batteries after annealing.
[0066] Comparative Example 1
[0067] In this comparative example, no Ga2O3 film is plated on the cut surface of the half-cell, and the remaining preparation steps and conditions are the same as those in Example 1.
[0068] Comparative Example 2
[0069] In this comparative example, the cut surface of the half-cell was not subjected to plasma treatment, and the remaining preparation steps and conditions were the same as those in Example 1.
[0070] Comparative Example 3
[0071] The thickness of the single-layer Al2O3 film in this comparative example is 70 nm, and the remaining preparation steps and conditions are the same as those in comparative example 1.
[0072] A group of half-cells without coating passivation treatment on the cut surface was added as a blank control group, and SunsVoc test and module power test were carried out together with the above-mentioned embodiment and comparative example, and AFM test was carried out on the above-mentioned embodiment 1 and comparative example 1 and comparative example 2. The detailed test results are as follows:
[0073] Table 1 SunsVoc test results
[0074]
[0075] It can be seen from Examples 1-3 that the use of the Ga2O3 / Al2O3 double-layer structure composite coating provided by the present invention can make the half-cell have a higher voltage value when the solar cell is not connected to a load, a higher fill factor and a lower base diffusion current, which indicates that the Ga2O3 / Al2O3 double-layer structure composite coating has an excellent passivation effect on the edge of the half-cell; from the test results of Comparative Examples 1 and 2, we can find that although the single-layer Al2O3 coating has improved the edge passivation repair of the half-cell, its passivation effect is still not as good as the Ga2O3 / Al2O3 double-layer structure composite coating, even if the Ga2O3 / Al2O3 double-layer structure composite coating is not subjected to plasma plasma treatment before coating, the passivation effect is still better than the single-layer Al2O3 coating subjected to plasma plasma treatment; in addition, combined with the test results of Comparative Example 3, we found that the Ga2O3 / Al2O3 double-layer structure composite coating provided by the present invention has a better repair effect than the 50-100nm thicker Al2O3 coating commonly used in the prior art.
[0076] Table 2 Component power test results
[0077]
[0078] From the test results of Examples 1-3 and Comparative Example 1 and the blank control group in Table 2, we can see that a series of performance indicators such as maximum power, fill factor, open circuit voltage and short circuit current of the half-cell battery coated with the Ga2O3 / Al2O3 double-layer structure composite coating are better than those of the half-cell battery coated with only a single layer of Al2O3 coating and the half-cell battery without edge passivation. This proves that the edge passivation method provided by the present application has a better effect on repairing the cut surface of the half-cell battery, making the half-cell battery have a higher power; and combined with Comparative Example 2, it can be seen that even if no plasma plasma is performed before coating, The performance of the Ga2O3 / Al2O3 double-layer structure composite coating treated by plasma is also better than that of the single-layer Al2O3 coating treated by plasma, which further proves that the Ga2O3 / Al2O3 double-layer structure composite coating provided by the present application has an excellent repair effect on the edge of the half-cell; in addition, combined with the test results of Comparative Example 3, we found that the Ga2O3 / Al2O3 double-layer structure composite coating provided by the present invention has a higher power than the half-cell prepared by the thicker Al2O3 coating of 50-100nm commonly used in the prior art.
[0079] Finally from Figure 1From the result graph of the AFM test, we can see that the half-cell cell provided in the present application, which is coated with a double-layer structure of Ga2O3 / Al2O3 composite film, has a smaller RMS and a smoother coating than the half-cell cell coated with only a single-layer Al2O3 film, which enhances the passivation effect of the Al2O3 film; and the double-layer structure of Ga2O3 / Al2O3 composite film, which is not subjected to plasma treatment before coating, is smoother than the single-layer Al2O3 film, which proves that coating the Ga2O3 film first can make the cut surface smoother, which helps to enhance the passivation effect of the subsequent Al2O3 coating at a relatively thin thickness.
[0080] The present invention adopts Ga2O3 / Al2O3 double-layer structure composite coating to passivate and repair the cut surface of the half-cell battery. Ga2O3 is a transparent conductive oxide material with excellent performance, large bandgap width, high breakdown field strength, and small on-resistance. Moreover, as an insulating material, Ga2O3 has high-k characteristics and can be used as a passivation film to eliminate or reduce interface states. In addition, the strong passivation of Ga2O3 can reduce the interface state of the cut surface of the half-cell battery while providing a flat plane for the subsequent deposition of the Al2O3 film, thereby greatly enhancing the passivation effect of the Al2O3 film, improving the passivation performance, reducing the pFF loss of the half-cell battery, and improving the power of the component.
[0081] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for edge passivation of a half-cell battery, characterized in that: The following steps are involved: Step 1: Cut the battery cell into half cells; Step 2: Clean the cut surface of the half-cell battery; Step 3: After cleaning, deposit Ga2O3 film layer and Al2O3 film layer on the cut surface of the half-cell in sequence; Step 4: Annealing the Ga2O3 film layer and the Al2O3 film layer; Step 5: Inspect, sort and package the half-cell batteries after annealing.
2. A method for edge passivation of a half-cell battery according to claim 1, characterized in that: An ALD deposition method is adopted, and a gallium source precursor and an oxygen source are used to deposit a Ga2O3 film layer on the cut surface of the half-cell. The thickness of the Ga2O3 film layer is 3-5 nm.
3. A method for edge passivation of a half-cell battery according to claim 2, characterized in that: The gallium source precursor is one or more of trimethylgallium, triethylgallium and gallium trichloride.
4. The method for edge passivation of a half-cell battery according to claim 1, characterized in that: An ALD deposition method is adopted, and an aluminum source precursor and an oxygen source are used to deposit an Al2O3 film layer on the surface of the Ga2O3 film layer, and the thickness of the Al2O3 film layer is 15-30nm.
5. A method for edge passivation of a half-cell battery according to claim 4, characterized in that: The aluminum source precursor is one or more of aluminum trichloride, trimethylaluminum and triethylaluminum.
6. A method for edge passivation of a half-cell battery according to any one of claims 2 or 4, characterized in that: The oxygen source is one or more of H2O, O2, and O3.
7. The method for edge passivation of a half-cell battery according to claim 1, characterized in that: The deposition temperature is 200-230° C., and the isolation gas used is one or more of helium, argon and nitrogen.
8. The method for edge passivation of a half-cell battery according to claim 1, characterized in that: The cutting of the battery cell comprises: using a pulsed laser to make grooves at both ends of the cutting line of the battery cell, and then using a continuous laser to heat the battery cell and atomizing and cooling the battery cell to obtain the half-cell battery.
9. The method for edge passivation of a half-cell battery according to claim 1, characterized in that: The cut surface of the half-cell is cleaned using plasma treatment.
10. The method for edge passivation of a half-cell battery according to claim 1, characterized in that: The annealing temperature is 250-300°C.